Seminar: "Latest Tax Modifications" - Medrano Cornejo, Humberto Félix (2014)
The present seminar deals about the last modifications occurred in the Peruvian normativity on tax matter. This analysis focuses on the last modifications occurred on Income Tax, Tax Code, Tax Drawdown regime and Municipal Taxation.